Development of natural seawater-based continuous biohydrogen production process using the hyperthermophilic archaeon Thermococcus onnurineus NA1. (29th October 2022) - Lee, Sung-Mok; Na, Jeong-Geol; Lee, Hyun Sook; Lee, Jung-Hyun; Kim, Tae Wan; Kang, Sung Gyun
Abstract: Previously, we reported that the hyperthermophilic archaeon, Thermococcus onnurineus NA1 could produce hydrogen from various resources including carbon monoxide (CO) with high productivity. In this study, a high-performance and cost-effective fermentation process was developed as a prerequisite for the industrial implementation of H2 production from CO using the strain. Firstly, an economical medium was formulated on the basis of natural seawater. Cysteine as a reducing agent was found to be an important factor to consider. Secondly, three variables, initial concentration of yeast extract, CO supply rate and agitation rate, were statistically optimized in batch culture by applying a response surface methodology. Notably, biomass productivity of 0.39 g/L/h could be observed and cell density reached 14 optical units at 600 nm, which is exceptionally high among members of the order Thermococcales . Finally, continuous cultures were tested at various dilution rates with new medium formulation and optimized culture conditions. As a result, the steady state of H2 production and cell growth were stably maintained, yielding H2 production rate of 471.5 mmol/L/h at a dilution rate of 0.1 h −1, which is one of the highest values at ambient CO pressure to date. Our study shows that T. onnurineus NA1 has outstanding potential as an economical and high performance industrial strain suitable for long-term processes for CO-dependent H2 production. Highlights: Natural seawater medium for gas (CO) fermentation of the hyperthermophilic archaeon, Thermococcus onnurineus NA1 was formulated. Gas fermentation variables on the medium formulation were statistically optimized in batch culture by applying a response surface methodology. Steady state of H2 production and cell growth were stably maintained with H2 production rate of 471.5 mmol/L/h, which is one of the highest values at ambient CO pressure to date. Biomass productivity and cell density were exceptionally high among members of the order Thermococcales.